UPAYA GURU DALAM MENGINTERNALISASIKAN NILAI – NILAI PENDIDIKAN AGAMA ISLAM BAGI PEMBENTUKAN AKHLAKUL KARIMAH DI SDIT AS SUNNAH KOTA CIREBON - Siti Muzianah (Pascasarjana UIN Siber Syekh Nurjati Cirebon, 2017)
Moral or character education is the responsibility of parents as the primary educators and the first of the children and everyone who is close to the students, including policy makers. Moral education in schools is the duty of the principal, teachers of religion, and all citizens of the school. Morals or character taught through methods internalisaai. Engineering education through imitation, habituation, guidance, enforcement of regulations, and motivating and not by way of explaining or discussing. This study discusses the research findings by the title